Formulation and in vitro/in vivo Evaluation of Control Targeted-release Budesonide Multi-unit Pellet Tablets for Colon Targeting - Borra, Syam Prasad (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim is to study the formulation and evaluation of budesonide multi-unit pellet tablets and is designed to release in both delayed and control release fashion with the objective of less in vitro and in vivo variability. Materials and Methods: Budesonide is class-II drug and insoluble in water. The major concerns with the budesonide are its poor solubility which results into poor drug release profiles and poor bioavailability after oral administration. Control release of drug and targeting to colon is another challenging, thereby reducing side effect, frequency of dose, and improved oral bioavailability and decreasing in vitro and in vivo variability. Micronization using high-pressure homonization milling with polysorbate 80 was chosen for improving solubility. Multi-unit pellet tablets technology was chosen for this purpose, and the optimal formulation was manufactured by suspension layering and solution layering methods in fluidized bed processor (FBP). The prepared MUPS tablets were tested for in vitro/in vivo performance. Results and Discussions: The in vitro drug release of the prepared formulation compared with marketed product showed similarity f2 = 65.18 in Ph 7.5 phosphate buffer, f2 = 70.13 in Ph 7.5 phosphate buffer with MCE, f2 = 65.05 in Ph 7.2 phosphate buffer, f2 = 60.30 in Ph 7.2 phosphate buffer without MCE to the marketed product, f2 = 53.34 in Ph 6.8 phosphate buffer, and f2 = 52.51 in Ph 6.8 phosphate buffer without surfactant. In pH 4.5, pH 6.0, and pH 6.5 media optimized formulation and marketed products, significant release was not observed. The pharmacokinetic study showed no significant difference (P > 0.05) in Cmax, AUC0-24 between the test and reference formulations observed, whereas subject variability observed more in reference formulation compared to test formulation. Conclusion: The obtained results suggested that micronization, MUPS technology with control release coating, and pH-dependent coating might be an efficacious approach for control release and targeted release of budesonide to colon with less in vitro and in vivo variability.